Self-perception of oral health in older adults from an urban population in Lisbon, Portugal - Catarina Carvalho; Ana Cristina Manso; Ana Escoval; Francisco Salvado; Carla Nunes (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To analyze if the self-perception of oral health in the urban context is associated with sociodemographic factors that interfere in the life quality of oral health. METHODS Cross-sectional study with convenience sample of older individuals (65 years old or more) enrolled in the Agrupamento de Centros de Saúde de Lisboa Norte (ACES Lisboa Norte - Health Centers Groupings North Lisbon). The self-perception of oral health and associated life quality was evaluated by the Geriatric Oral Health Assessment Index and the individuals were classified according to sociodemographic characteristics. The internal consistency of the questionnaire was evaluated by Cronbach's alpha (α). Later, we used binary logistic regression models to characterize the factors associated with the self-perception of oral health, considering the sociodemographic variables and the older adults' clinical conditions of oral health and establishing the crude and adjusted (to age) odds ratios and their 90% confidence intervals. RESULTS A total of 369 older adults participated in this study, with an average age of 74.2 years (SD = 6.75); 62.9% were female. On average, the index was moderated, with tendency to be high: 32.9 (SD = 3.6; 12-36 interval). The Cronbach's alpha was high: 0.805. Age, marital status, and the last dental appointment were the factors significantly associated with self-perception of oral health. CONCLUSIONS The study shows that these individuals have a moderate, with tendency to high, self-perception of oral health. The self-perception of oral health assessment allowed us to identify the main associated sociodemographic factors. This instrument can help guiding planning strategies and oral health promotion directed toward a better life quality for this population group.